2015
DOI: 10.1128/jvi.01487-15
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleolar Protein, Ribosomal RNA Processing 1 Homolog B (RRP1B), Enhances the Recruitment of Cellular mRNA in Influenza Virus Transcription

Abstract: Influenza A virus (IAV) undergoes RNA transcription by a unique capped-mRNA-dependent transcription, which is carried out by the viral RNA-dependent RNA polymerase (RdRp), consisting of the viral PA, PB1, and PB2 proteins. However, how the viral RdRp utilizes cellular factors for virus transcription is not clear. Previously, we conducted a genome-wide pooled short hairpin RNA (shRNA) screen to identify host factors important for influenza A virus replication. Ribosomal RNA processing 1 homolog B (RRP1B) was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
(43 reference statements)
1
23
0
1
Order By: Relevance
“…Identification of ZBTB25 as a positive regulator of IAV replication. To identify cellular regulators involved in IAV replication, our group previously utilized a highthroughput pooled RNA interference (RNAi) library screen to search for potential candidate genes (31)(32)(33). In this study, a secondary RNAi screening was performed to confirm these genes.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of ZBTB25 as a positive regulator of IAV replication. To identify cellular regulators involved in IAV replication, our group previously utilized a highthroughput pooled RNA interference (RNAi) library screen to search for potential candidate genes (31)(32)(33). In this study, a secondary RNAi screening was performed to confirm these genes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that there is an intense functional interplay between IAV and nucleoli ( 25 , 58 ). IAV vRNP hijacks the nucleolar proteins, such as NCL, NPM1, RRP1B, and some ribosomal proteins, to facilitate virus transcription and replication, or vRNP nuclear export ( 25 28 ), of which rRNA processing 1 homolog B (RRP1B) interacts with PB1 and PB2, enhancing viral transcription ( 27 ). NPM1 interacts with reconstituted vRNP, promoting viral polymerase activity ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleolus is known to be the site of rRNA gene transcription, rRNA processing, and assembly into preribosomal subunits ( 22 , 23 ), and its nonclassical functions include mRNA transport, sequestration of regulation complex, and regulation of cellular metabolism and cellular stress responses ( 24 ). IAV also interacts with the nucleoli to usurp host cell functions and recruits nucleolar proteins to aid its replication in the nucleus; in particular, the vRNP hijacks many nucleolar proteins for its function ( 25 27 ). Mayer et al identified 45 cellular proteins interacting with vRNP or polymerase ( 28 ); 11 of them are nucleolar proteins, including the two major constitutive proteins of the nucleolus, nucleolin (NCL or C23) and nucleophosmin (NPM1 or B23), and ribosomal proteins, some of which have also been identified by others using similar proteomic approaches or other experiments ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, both nucleolar proteins of ribosomal RNA processing 1 homolog B (RRP1B) and nucleolin are involved in ribosomal biogenesis (Chamousset et al 2010 ). RRP1B associated with pre-60S ribosomal subunits was translocated to the nucleoplasm upon viral infection of influenza virus, where RRP1B improves viral RNA-dependent RNA polymerase (RdRp) activity, which is responsible for virus transcription and replication (Su et al 2015 ). Nucleolin, which is thought to control RNA metabolism and ribosome biogenesis (Cong, et al 2012 ; Allain 2000 ), is prevented from entering the nucleus in poliovirus-infected cells (Waggoner 1998 ); this allows stimulation of IRES-mediated translation of viral transcripts (Izumi 2001 ).…”
Section: The Roles Of Ribosome Biogenesis In Viral Replicationmentioning
confidence: 99%